Systematic Literature Review: Identification of Interleukin-10 in Mesenchymal Stem Cells for Inflammation - Vika Amelia; Irfan Suliansyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mesenchymal stem cell is a technology that is immunodulatory which is able to repair tissue damage in the skin and overcome various inflammatory diseases. One of the cytokines that can repair tissue damage and overcome inflammation is interleukin-10. The purpose of this research to to systematically review the literature on science trends, knowledge and publication, especially the identification of interleukin-10 in mesenchymal stem cells using bibliometric analysis. A total of one hundread journals obtained from the Google Scholar database for 2016 – 2023 were used in this study. To find out the overall trend on this research topic, the keywords (Mesenchymal stem cell, interleukin-10 and inflammation) that often appear in journal publication are then visualized and mapped using application Vosviewer software. The results showed that there was an increase in research of identification interleukin-10 in Mesenchymal stem cells in various journals as well as research on the characterization and utilization of Mesenchymal stem cells in skin regeneration.